Peningkatan Kompetensi Guru Pesantren Melalui Pendampingan Pembuatan Buku Ajar Kreatif Dan Inovatif - Saleh Dwiyatno; Erni Krisnaningsih; Sulistiyono; Rita Wiji Wahyuningrum; Anita Dyah Juniarti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Textbooks are very important in the learning process because they can support and strengthen the information of teaching materials delivered by teachers. Textbooks help students understand the concepts of science to achieve the desired competencies so that they are easy to understand which is needed in learning because they can explain various difficult phenomena including abstract concepts to become realistic knowledge to make students motivated to learn. Textbooks are very effectively used as a learning medium because they function as a tool for accurate information communication from teachers to students. Using good textbooks will accelerate the achievement of competencies to achieve the role of a good teacher, objective, and relevant truths. The purpose of this community service activity (CSA) is to increase the competence of Islamic boarding school teachers through assistance in making creative and innovative digital textbooks based on multimedia with Flip PDF. To achieve this goal, training activities (workshops), discussion activities for needs and assistance as well as the benefits of making creative and innovative digital textbooks in supporting learning activities are carried out. The material presented during the CSA activity received a good and positive response from the participants of the mentoring activity and stated that the mentoring activities that had been carried out needed to be continued in the future. For the next km implementation, we propose assistance in the implementation of e-Learning.